Perkembangan Persuratkhabaran Bahasa Mandarin di Malaysia dan Peranannya Dalam Masyarakat Cina - Lee, Kuok Tiung; Mohd Safar Hasim; Baszley Bee Basrah Bee (2011)
The establishment of Chinese newspapers in Malaysia began with the migration of overseas Chinese (Huaqiao) to Malaysia. Several of the pioneer Chinese newspapers such as Kwong Wah Yit Poh (1910), Nanyang Siang Pau(1923), Sin Chew Jit Poh (1929), Overseas Chinese Daily News (1932), and China Press (1946) are still in existence today. This article explores the development of the Chinese newspapers by tracing their chronology; analyses the factors that contributed to the emergence of the newspapers, and identifies their challenges. A salient aspect of the contemporary mediascape pertaining to Chinese newspapers is the ownership of the newspapers. In the past, the ownership of newspapers revolved around individual companies, whereas, majority of the newspapers in Malaysia now are owned by two Chinese tycoons, both from Sarawak, through Media Chinese International Limited (MCIL) and Kumpulan KTS. This article will show how the Chinese newspapers played a crucial role in advocating and fighting for Chinese education,culture and identity.